Assessment of enamel cracks at adhesive cavosurface margin using three-dimensional swept-source optical coherence tomography. (June 2017) - Tabata, Tomoko; Shimada, Yasushi; Sadr, Alireza; Tagami, Junji; Sumi, Yasunori
Abstract: Objectives: Swept-source optical coherence tomography (SS-OCT) can construct cross-sectional images of internal biological structures. The aim of this study was to evaluate enamel cracks at the cavosurface margin of composite restorations using SS-OCT. Methods: Bowl-shaped cavities were prepared at two locations (mid-coronal and cervical regions) on the enamel surface of 60 bovine teeth. Half of the cavities (30) were treated with phosphoric acid gel. A two-step self-etch adhesive (Clearfil SE Bond) was applied to all cavities and a flowable composite was placed in bulk. After 7 days in water at 37 °C, three-dimensional (3D) images of the specimens were obtained using SS-OCT, and cross-sectional views of the cavosurface margin were examined. Presence and extent of enamel cracks along the cavosurface margin circumference were evaluated using a 5-point scale. The results were statistically compared with Wilcoxon rank sum test with Bonferroni correction. Results: 3D SS-OCT could detect enamel cracks at the cavosurface margin of composite restorations. Cervical regions caused more enamel cracking than mid-coronal regions. Phosphoric acid etching increased the incidence of enamel cracks compared with the preparations without etching. Conclusion: SS-OCT can be used to detect enamel cracks at the margins of composite restorations noninvasively. Presence and extent of enamel cracks depended on the enamel region and bonding protocol. Clinical significance: SS-OCT can be used to detect enamel cracks at the margins of composite restorations noninvasively. Selective phosphoric acid etching of the enamel significantly increased the incidence of marginal cracks, especially in cervical preparation.